Observation of 27 day solar cycles in the production and mesospheric descent of EPP‐produced NO. Issue 10 (20th October 2015) - Hendrickx, K.; Megner, L.; Gumbel, J.; Siskind, D. E.; Orsolini, Y. J.; Tyssøy, H. Nesse; Hervig, M.
Abstract: Nitric oxide (NO) is produced by energetic particle precipitation (EPP) in the mesosphere‐lower thermosphere (MLT) region, and during the polar winter, NO can descend to stratospheric altitudes where it destroys ozone. In this paper, we study the general scenario, as opposed to a case study, of NO production in the thermosphere due to energetic particles in the auroral region. We first investigate the relationship between NO production and two geomagnetic indices. The analysis indicates that the auroral electrojet index is a more suitable proxy for EPP‐produced NO than the typically used midlatitude A p index. In order to study the production and downward transport of NO from the lower thermosphere to the mesosphere, we perform superposed epoch analyses on NO observations made by the Solar Occultation For Ice Experiment instrument on board the Aeronomy of Ice in the Mesosphere satellite. The epoch analysis clearly shows the impact of the 27 day solar cycle on NO production. The effect is observed down to an altitude range of about 50 km to 65 km, depending on the hemisphere and the occurrence of stratospheric warmings. Initially, a rapid downward transport is noted during the first 10 days after EPP onset to an altitude of about 80–85 km, which is then followed by a slower downward transport of approximately 1–1.2 km/d to lower mesospheric altitudes in the order of 30 days. Key Points: Clear 27 day solar signal in nitric oxide due to EPP production Epoch analysis shows the NO descent from the lower thermosphere to the mesosphere Suggestion as proxy for auroral electron precipitation: AE superior to Ap index